Description of Alloretochus sigillatus new species with comments and new distributional records for Alloretochus peruanicus (Ephemeroptera, Caenidae, Brachycercinae) - Molineri, C. (Zootaxa, 2014)
Alloretochus sigillatus sp. nov. is described from adults of both sexes and eggs from Bolivia and Ecuador. Diagnostic characters of this species include: large body size, ratio pedicel/scape 1.75, presence of posteromedian projection on metanotum, characteristic blackish marks on abdominal terga, presence of vestiges of posterolateral projections on abdomen segments IV–VI, male subgenital plate broadly emarginated posteriorly, ratios forceps length/subbasal width 8.9, female sternum IX produced distally reaching apex of segment X, tapering distally with rounded apex, egg with 4 costae in lateral half. Additional characters for all stages and SEM photographs of eggs are provided for Alloretochus peruanicus, with new records of its presence in Argentina, Bolivia, Peru and Colombia.